Nas margens e nas bordas: dissenso e autonomia em torno do Ribeirão Onça - José Camilo Carlos Júnior (2022)
This research emerges from concerns about the daily articulations and conflicts of groups which coexist in environmentally fragile urban margins. I investigate the production of spatial types, in the Ribeiro de Abreu neighborhood, located in the margins and proximities of the natural riverbed of Ribeirão Onça, in Belo Horizonte. The central objective of this research is to understand how the production of peripheral everyday space occurs and how it results in different practices, obstacles, and conflicts experienced by and between groups that are spati-ally close to each other. The coexistence of groups considered marginal, on the urban outskirts, provides unique forms of solidarity and alterity, as well as interaction with nature. Thus, I have articulated field work and documentary research to systematize how the genesis and consolidation of these spatial types came about, and how the forms of organization and mobilization of their inhabitants take place. The groups engaged around Ribeirão Onça have challenged the boundaries and dichotomies between urban and nature, based on their everyday experiences and their claims regarding the transformation of the built space and the depletion of wa-terways. These are aspects that show potentialities for thinking about other ways of living and interacting with humans and non-humans.